(untitled) (Anwer Khan Modern Medical College Journal, 2014)
This study was conducted to understand the infant (0-12 month) feeding practices among different classes’ mothers in Dhaka city. The study was carried out among the 183 mother-infant pair of the upper, middle and lower socio-economic classes in Dhaka city and purposive sampling method was applied. The study was conducted at following areas in Dhaka city which were selected purposively. The mean age of upper class, middle class and lower class were 35±4, 25±3 and 21±7 in years. Regarding first feeding it was observed that upper (75%), middle (85%) and lower class (48%) first gave colostrum. It also observed that 18% of upper class mother first gave powder milk, while in case of middle class it was 5%. In lower class preference of giving honey and sugar water were 21% and 12% respectively. The starting time of breast feeding indicated that in upper classes (74%) breast feeding initiated within one hour, while in middle (75%) and lower classes (84%) it was given within 12 hours. It was highlighted that 44% upper and 36% lower class mothers started complementary feeding at 3 month of the baby respectively, while in middle class 61% mother started complementary foods at 5 month of their baby. In case of duration of breast feeding practices, middle and lower classes breast-feed continued longer time than upper class. Majorities of the upper class prefered egg, soup, fruit juice while middle class liked meat-fish, egg, khichuri, fruits. On complementary feeding the lower class choiced mainly rice-potato, dal, khichuri or vegetables. The study result should not be generalise and need further large scale research. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21124 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 5-8